Contribution to the global air–sea CO2 exchange budget from asymmetric bubble-mediated gas transfer - Xin Zhang (Tellus: Series B, Chemical and Physical Meteorology, 2012)
Quantifying air–sea gas exchange is an essential element for predicting climate change due to human activities. Air–sea gas exchanges take place through both the sea surface and bubbles formed during wave breakings. Bubble-mediated gas transfers are particularly important at high wind regions. Bubble-mediated gas transfers are separated into symmetric and asymmetric transfers. Their transfer fluxes are respectively proportional to the gas concentration difference between the atmosphere and ocean surface water, and to the atmospheric gas concentration alone. To quantify the role of asymmetric transfers in the global carbon dioxide (CO2) transfer budget, a parameterisation scheme of asymmetric transfer is developed, which is constrained by gas equilibrium supersaturation in the ocean surface. By establishing a bound for the global mean gas equilibrium supersaturation in ocean surface water, we found that the global ocean uptake by bubble-mediated asymmetric gas transfer is a substantial part of the total air–sea CO2 uptake budget (over 20%). It is found that, over the past half century, the global asymmetric ocean CO2 uptake has increased about a total of 40% on a steadily trend, as a consequence of the increasing atmospheric CO2 concentrations.